Engineers turn to e-learning. - Ubell, R. (IEEE spectrum)
Learning online is one of the strongest currents in higher education, as the working engineer in particular is discovering. This paper details how, in the coming years, technological advances, such as wireless networking, will undoubtedly help make e-learning more attractive. And as high-speed, broadband Internet connections become the norm, more real-time, interactive uses of the Web will appear in online-learning classes